Bioengineered bile ducts recapitulate key cholangiocyte functions. (12th June 2018) - Chen, Chen; Jochems, Paulus G M; Salz, Lucia; Schneeberger, Kerstin; Penning, Louis C; van de Graaf, Stan F J; Beuers, Ulrich; Clevers, Hans; Geijsen, Niels; Masereeuw, Rosalinde; Spee, Bart
Abstract: Investigation of diseases of the bile duct system and identification of potential therapeutic targets are hampered by the lack of tractable in vitro systems to model cholangiocyte biology. Here, we show a step-wise method for the differentiation of murine Lgr5 + liver stem cells (organoids) into cholangiocyte-like cells (CLCs) using a combination of growth factors and extracellular matrix components. Organoid-derived CLCs display key properties of primary cholangiocytes, such as expressing cholangiocyte markers, forming primary cilia, transporting small molecules and responding to farnesoid X receptor agonist. Integration of organoid-derived cholangiocytes with collagen-coated polyethersulfone hollow fiber membranes yielded bioengineered bile ducts that morphologically resembled native bile ducts and possessed polarized bile acid transport activity. As such, we present a novel in vitro model for studying and therapeutically modulating cholangiocyte function.